JITT with assessment for learning: Investigation and improvement of students understanding of kinematics concept - Akhmad Jufriadi; Ratri Andinisari (Momentum: Physics Education Journal, 2020)
This study aims to investigate and explore students' understanding of the concept of Kinematics, particularly in the concepts of acceleration, velocity, distance and displacement. This research used a mixed-method approach with an embedded experimental design. The research was conducted by involving 21 students consisting of 7 men and 14 women. This research used reasoned multiple-choice questions and short interviews to determine the students' initial and final understanding. The results showed that, before the intervention was carried out, as much as 42.86% of students did not understand the concept of distance and displacement correctly, as much as 26.99% of students did not understand the concepts of instantaneous velocity and average speed, as much as 45.6% did not understand the concepts of position, velocity and acceleration and as much as 87.31% did not understand about the direction of velocity and acceleration. In addition, the results showed that the application of JITT with assessment for learning could significantly improve students' understanding of concepts, with N-gain = 0.56 and effect size = 2.38. This study explains the difficulties and general understanding of students on the concepts of distance and displacement, and the direction of object acceleration. In addition, the integration of assessment for learning to JITT is an option in the learning process to improve understanding of Kinematics concepts.